Practical support for ISO 9001 software project documentation using IEEE software engineering standards - Land, Susan K. (Wiley-IEEE Computer Society,John Wiley [distributor], 2006)
This book addresses how to meet the specific documentation requirements in support of the ISO 9001 software process definition, documentation, and improvement, which is an integral part of every software engineering effort.Provides a set of templates that support the documentation required for basic software project control and management.The book provides specific support for organizations that are pursuing software process improvement efforts,